Japanese Persimmon Cultural Practices in Florida - Ali Sarkhosh; Dustin M. Huff; Peter C. Andersen (EDIS)
Persimmons are considered a relatively sustainable crop in Florida, rated as a 6 out of 10 on an assessment of agricultural sustainability, with a moderate commercial potential and high direct-to-consumer potential. Trees grow and fruit best in central and northern Florida and can produce high yields of good-quality fruit. This new 13-page publication of the UF/IFAS Horticultural Sciences Department describes how to propagate and establish persimmons in Florida, while also providing information on irrigation, fertilization, harvest, pests, diseases, and more. Written by Ali Sarkhosh, Dustin M. Huff, and Peter C. Andersen. https://edis.ifas.ufl.edu/hs1389